Proceedings of the international conference on aerospace system science and engineering 2020 - Jing, Zhongliang; Zhan, Xingqun (Singapore Springer, 2021)
This book presents high-quality contributions in the subject area of Aerospace System Science and Engineering, including topics such as: Trans-space vehicle systems design and integration, Air vehicle systems, Space vehicle systems, Near-space vehicle systems, Opto-electronic system, Aerospace robotics and unmanned system, Aerospace robotics and unmanned system, Communication, navigation, and surveillance, Dynamics and control, Intelligent sensing and information fusion, Aerodynamics and aircraft design, Aerospace propulsion, Avionics system, Air traffic management, Earth observation, Deep space exploration, and Bionic micro-aircraft/spacecraft. The book collects selected papers presented at the 4th International Conference on Aerospace System Science and Engineering (ICASSE 2020), organized by Shanghai Jiao Tong University, China, held on 14–16 July 2020 as virtual event due to COVID-19. It provides a forum for experts in aeronautics and astronautics to share new ideas and findings. ICASSE conferences have been organized annually since 2017 and hosted in Shanghai, Moscow, and Toronto in turn, where the three regional editors of the journal Aerospace Systems are located.
Electronic reproduction
Keywords: Aerospace engineering -- Congresses; Electronic books